PROHIBITION SPEECH ACTS OF GUS BAHA AND USTADZ ABDUL SOMAD IN ISLAMIC PREACHING - Urohmah, Annisa Aulia; Ratnadewi, Dwijani; Ro'ifah, Ro'ifah (Universitas PGRI Sumatera Barat, 2024)
Prohibition speech acts of religious preachers is an interesting topic research because it is not like that of other people's speech acts which always be modified according to interests, preachers’ language but must be clear, unambiguous and without raising different interpretations. The aim of this research is to find types, meaning, and comparison of Gus Baha’s (GB) and Ustadz Abdul Somad’s (UAS) prohibition speech acts. The design of this research is qualitative descriptive with the data collection techniques: downloading and selecting videos from youtube. To obtain data, the key instrument was the researcher herself. Data in this study were utterances containing prohibition speech acts in 6 YouTube of GB’s and UAS’ Islamic preaching. The data were analyzed based on Pragmatics, Speech Act, Politeness, and Context theories. The findings were GB used Off Record (Rhetorical Questions), Positive Politeness (Assuming or emphasizing reciprocity), and Negative Politeness (Being Conventionally Indirect). Meanwhile, UAS uses the Off Record strategy (Metaphor and Use of Contradiction) and Negative Politeness (Intensifying Interest in H). The preachers similarly used the Bald On Record and Positive Politeness (Notice). The politeness strategy applied is able to reveal the similarities and differences in the choice of prohibition speech acts from both preachers.